The «Islamic State»: The Path to The Self-Proclamation of a Contemporary Caliphate - Rooney, Mildred (2016)
In only two years, since proclaimed it-self as a «Califate», the Islamic State has experienced an accelerated ideological, territorial and cybernetic expansion, which has led to a wave of bloody sectarian violence against non-Sunni populations. In a short time, it has managed to control large areas in Iraq and Syria where runs a political-religious administration founded on fundamentalist interpretation of the sharia. The characteristics of its organization, methodsand objectives obscure its understanding, and therefore also the design of strategies for efficient combating. This article intends to understand the genesis and expansion of this nonstate actor, its administrative and military capabilities, and self-financing; also, determine its strategy and factors that explain «media success»; explain its hybrid nature; and finally discuss the implications of its emergence in the regional dynamics, characterised by political and religiousrivalry between the representatives of the Sunni faction, Turkey and Saudi Arabia; and Shi’ite Iran. In this context convulsed by terrorism, insurgency, and the struggle for regional leadership, the Kurdish nation could find the conditions to achieve Kurdistan.